2005
DOI: 10.1152/ajpendo.00092.2005
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of adipose tissue lipolysis increases intramuscular lipid and glycogen use in vivo in humans

Abstract: This study investigates the consequences of inhibition of adipose tissue lipolysis on skeletal muscle substrate use. Ten subjects were studied at rest and during exercise and subsequent recovery under normal, fasting conditions (control trial, CON) and following administration of a nicotinic acid analog (low plasma free fatty acid trial, LFA). Continuous [U- 13 C]palmitate and [6, H2]glucose infusions were applied to quantify plasma free fatty acid (FFA) and glucose oxidation rates and to estimate intramuscula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
61
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 65 publications
8
61
0
Order By: Relevance
“…In the present study, TG content in the soleus muscle was considerably (3-5 times) higher than those in the other muscles in both experiments. Our results supported the previous findings [8][9][10]13,25) , but the prolonged swimming, even for 4 h, did not reduce the TG contents of the soleus muscle in either experiment at all. In the present study, it is not clear whether or not MTG was utilized as an energy substrate, because the MTG contents were not measured directly.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, TG content in the soleus muscle was considerably (3-5 times) higher than those in the other muscles in both experiments. Our results supported the previous findings [8][9][10]13,25) , but the prolonged swimming, even for 4 h, did not reduce the TG contents of the soleus muscle in either experiment at all. In the present study, it is not clear whether or not MTG was utilized as an energy substrate, because the MTG contents were not measured directly.…”
Section: Discussionsupporting
confidence: 92%
“…As well as these previous old reports, van Loon 10) demonstrated more than 60% net decline in type-I muscle fiber lipid content following 120 min of exercise. It has been well known that red-type muscles contain about three times more lipids than white-type muscles [8][9][10]13,25) . It was also reported that the reduction rate of TG in red muscles during exhaustive exercise was also considerably higher than that in white muscles 8,11,12) , indicating that muscle fat oxidation was noticeably higher in red muscles contained more mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is plausible that we have underestimated the potential for fatty acids to support muscle energy metabolism (35,36), as we did not specifically enrich the perfusate with free fatty acids in the present study (although intramuscular stores would be plentiful). It would seem, from the higher oxygen consumption and lower glucose and glycogen utilization, that muscle lipid utilization must have been increased to some extent.…”
Section: Discussionmentioning
confidence: 97%
“…Infact, exercise training involves multiple metabolic adaptations including increased preexercise skeletal muscle glycogen content, enhanced activity of key enzymes involved in the -oxidation [117], increased sensitivity of adipose tissue to epinephrine-stimulated lipolysis [118], and increased oxidation of intramuscular triglycerides [119], whereby the capacity to oxidize fat is increased [120]. As a consequence, the trained skeletal muscle is less dependent on plasma glucose and muscle glycogen as substrate during exercise [121].…”
Section: Part II -Effect Of a Single Bout Of Exercise On Inflammatorymentioning
confidence: 99%